REKONFIRMASI LEGITIMASI RUU KEADILAN DAN KESETARAAN GENDER PERSPEKTIF MAQOSHID SYARIAH - Suhaeri, Suhaeri (Musawa Jurnal Studi Gender dan Islam, 2015)
Ratification of the Justice and Gender Equality (KKG) bill has been delayed since its inception  on August 24, 2011. The bill has not been passed in legislation by the Parliament allegedly due to the harsh response of many people, especially Moslems, who consider the KKG bill contrary to the teachings and religious values   of Islam, and laden with western ideology and culture. Is the KKG bill legitimate? This article attempts to situate the debate over the proposed KKG bill by reviewing the reasons of the two opposing maqashid Sharia methods.